An Assessment of Women’s Participation in South Africa’s Foreign Policy Decision-Making and Execution - Ipeleng Mamokete Nwafor; Lere Amusan (Politicon : Jurnal Ilmu Politik, 2022)
This study aims to assess women's participation in decision-making and implementation of South African foreign policy. This research is motivated by the significant dominance of male gender participation and leadership in DIRCO related to female participation since 1994. This study uses Intersectionality theory and Kanter's Theory to support this research with qualitative methods. The findings of this study indicate that women's participation is less than 50% when they hold junior positions. It found that challenges limiting women's involvement in foreign policy decision-making include unfavorable cultural and traditional norms, religious practices, lack of support for women, attitudes of influential men, financial problems, and lack of representation in politics.